The pathophysiology of extracellular hemoglobin associated with enhanced oxidative reactions - Rifkind, Joseph M.; Mohanty, Joy G.; Nagababu, Enika (Frontiers in Physiology, 2015)
Hemoglobin (Hb) continuously undergoes autoxidation producing superoxide which dismutates into hydrogen peroxide (H2O2) and is a potential source for subsequent oxidative reactions. Autoxidation is most pronounced under hypoxic conditions in the microcirculation and for unstable dimers formed at reduced Hb concentrations. In the red blood cell (RBC), oxidative reactions are inhibited by an extensive antioxidant system. For extracellular Hb, whether from hemolysis of RBCs and/or the infusion of Hb-based blood substitutes, the oxidative reactions are not completely neutralized by the available antioxidant system. Un-neutralized H2O2 oxidizes ferrous and ferric Hbs to Fe(IV)-ferrylHb and oxyferrylHb, respectively. FerrylHb further reacts with H2O2 producing heme degradation products and free iron. OxyferrylHb, in addition to Fe(IV) contains a free radical that can undergo additional oxidative reactions. Fe(III)Hb produced during Hb autoxidation also readily releases heme, an additional source for oxidative stress. These oxidation products are a potential source for oxidative reactions in the plasma, but to a greater extent when the lower molecular weight Hb dimers enter cells and tissues. Heme and oxyferryl have been shown to have a proinflammatory effect further increasing their potential for oxidative stress. These oxidative reactions contribute to a number of pathological situations including atherosclerosis, kidney malfunction, sickle cell disease and malaria. The toxic effects of extracellular Hb are of particular concern for increased hemolysis due to hemolytic anemia. Hemolysis is further exacerbated in various diseases and their treatments. Blood transfusions are required whenever there is an appreciable decrease in RBCs due to hemolysis or blood loss. It is, therefore, essential that transfused blood, whether stored RBCs or blood obtained by an Autologous Blood Recovery System from the patient, does not further increase extracellular Hb.